2021
DOI: 10.1007/s00066-021-01865-3
|View full text |Cite|
|
Sign up to set email alerts
|

The impact of nutritional counseling on thyroid disorders in head and neck cancer patients after (chemo)radiotherapy: results from a prospective interventional trial

Abstract: Objective To analyze the impact of nutritional counseling on the development of hypothyroidism after (chemo)radiotherapy in head and neck cancer patients to propose a new normal tissue complication probability (NTCP) model. Materials and methods At baseline, at the end of (chemo)radiotherapy, and during follow-up, thyroid-stimulating hormone (TSH) with free thyroxin (fT3 and fT4), nutritional status, and nutrient intake were prospectively analyzed in 46 ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
(90 reference statements)
0
3
0
Order By: Relevance
“…The impact of nutritional counselling alone on nutritional status of HNC patients during radiochemotherapy is hard to predict, as recent studies found either no [ 49 ] or a significant difference to the no-counselling group [ 50 ]. A better strategy appears to be nutritional counselling plus the delivery of calorie-dense, high-protein, and omega‑3 fatty acid-enriched supplements, which was shown to lead to significantly less BM loss than nutritional counselling alone [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The impact of nutritional counselling alone on nutritional status of HNC patients during radiochemotherapy is hard to predict, as recent studies found either no [ 49 ] or a significant difference to the no-counselling group [ 50 ]. A better strategy appears to be nutritional counselling plus the delivery of calorie-dense, high-protein, and omega‑3 fatty acid-enriched supplements, which was shown to lead to significantly less BM loss than nutritional counselling alone [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data on our therapy procedure have previously been published [ 7 9 ]. Briefly, patients were referred to our department for either definitive or adjuvant radiotherapy (IMRT with 1.7–2.0 Gy, 5 times/week, to cumulative doses ranging from 60–70.4 Gy [ 10 , 11 ]) alone or combined chemoradiotherapy with mainly cisplatin (100 mg/m 2 3‑weekly or 40 mg/m 2 weekly) or with 5‑fluorouracil (5-FU)/mitomycin C (MMC) (600 mg/m 2 on days 1–5 and 10 mg/m 2 on days 5 and 36, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…Curative treatment of elderly HNC patients often requires multimodal approaches including surgery, radiotherapy (RT), or concomitant chemoradiation (CRT), but therapy is often complicated by reduced patient performance or comorbidities. Additionally, treatment-related toxicities commonly require intensified medical procedures and additional supportive care in elderly patients, resulting in substantial healthcare resource requirements and costs [3][4][5][6]. In this respect, it is important to compare increased treatment-related costs to benefits in treatment outcomes and patients' health-related quality of life (HRQoL) [7][8][9].…”
Section: Introductionmentioning
confidence: 99%